Co‐creation of five key research priorities across law enforcement and public health: A methodological example and outcomes. Issue 1 (13th July 2020) - Murray, Jennifer; Heyman, Inga; Dougall, Nadine; Wooff, Andrew; Aston, Elizabeth; Enang, Iniobong
Accessible summary: What is known on the subject?: Between policing and health, there are many shared issues. Mental health distress and crises and caring for people who may be vulnerable are priority areas. Working together in partnership is challenging, and fragmented systems and processes are the result. This leads to poor experiences for the police, health professions and the public. What the paper adds to existing knowledge?: This paper describes an event that brought together 26 stakeholders involved in law enforcement and public health. The aim of this work was to identify the biggest shared challenges that they experience in their day to day jobs. The five key priorities were as follows: vulnerability; mental health crisis; decision‐making around assessment and triage across professional groups and professional roles; peer support and organizational well‐being; and information and data sharing. What are the implications for practice?: This paper demonstrates the strength of bringing partners together throughout law enforcement and public health, making proper time to actually discuss the "big issues" which affect them, how they each experience these issues, and how they might have overcome these within their own professions. Only through working together as partners and having everyone on the same page with the shared priorities can we really start to make a difference in the areas and with the people who matter. The focus on "vulnerability" and "mental health crisis" demonstrates the complexity of the issues between the professions, and that they need to find effective ways to work together to support people. No one professional group can solve inter‐professional challenges alone. Abstract: Introduction: Law enforcement professions now assume more responsibility for tackling mental health issues alongside public health colleagues than ever before. The term "vulnerability" is frequently used within Law Enforcement and Public Health (LEPH) to identify those requiring emergency mental health care. However, there are ongoing challenges within LEPH to determine whose responsibility this is. Aim: To co‐create the most important priorities for LEPH research in Scotland. Method: The paper describes a collaborative workshop which brought together an Expert Advisory Group (EAG) of 26 senior stakeholders, from academia, policing, mental health nursing, psychiatry, paramedics, emergency medicine, people with lived experience, policy makers and third sector. Results: The five key priorities included: vulnerability; mental health crisis; decision‐making around assessment and triage across professional groups and professional roles; peer support and organizational well‐being; and information and data sharing. Discussion: The paper discusses the EAG group event as a co‐production process, focusing on how key LEPH research priorities were derived. Implications for practice: This paper demonstrates the inextricable link between co‐production and co‐creation of value via EAG group consensus on LEPH research priorities. Shared vision and professional will are not enough to ensure progress: there must also be shared policy, knowledge and access.